Implementing strong sustainability in a design process - Melissa Escobar Cisternas; Jenny Faucheu; Nadege Troussier; Valerie Laforest (Cleaner Environmental Systems)
The emergence of a post-growth era is expected that implies rethinking the production and consumption patterns with novel design models this forces higher educational institutions to reconsider their traditional ways of teaching sustainability in their curricula. Companies also need to overcome strategies that compartmentalize environment, society and economy in their industrial strategy in order to evolve in their support for the transition. The aim of this paper is to present a design process anchored in the Strong Sustainability paradigm to overcome the gap of how Strong Sustainability could be operationalised. Design Research Methodology (DRM) has been chosen as the supporting framework for the development of this project. The Design for Strong Sustainability (DfSoSy) methodology proposed, is built on three aspects of Strong Sustainability (Milieu, Regeneration, Safe and just operating space) successively applied in a sequenced iterative design process. The latter enable the integration of thought patterns associated with integrative, systemic and fractal or multi-scale thinking respectively. Moreover, the principle of sub-optimality is highlighted as a decision principle in SoSy. Results obtain has been validated as well on the pedagogical objectives as in the usefulness of the DfSoSy. The practical contribution of this study is the DfSoSy toolkit©.